The influence of information status on pronoun resolution in Mandarin Chinese: evidence from ERPs - Xu, Xiaodong (Frontiers in Psychology, 2015)
The purpose of this study is to shed light on the neural mechanisms underlying the modulation of pronoun resolution processes by the information status of the antecedent. Information status was manipulated by using a structurally-based constraint (e.g., order of mention) as well as a pragmatically-based constraint (i.e., topichood). We found that the pronouns referring to topic entities (the initial NP in SOV structure in Experiment 1 and OSV structure in Experiment 2) elicited attenuated P600 responses compared to the pronouns referring to non-topic entities (the initial NP in SVO structure or the second NP in OSV structure in both experiments) when potential interference from structural constraints was controlled. The linear structural constraint, namely the order of mention, had no clear influence on the P600 effect when the syntactic structural constraint was held constant (i.e., when both entities were syntactic subjects), regardless of whether one (Experiment 1) or two (Experiment 2) animate antecedents were present. These findings suggest that pragmatically encoded features such as topichood and givenness can be processed separately from structural constraints such as order of mention to promote the salient status of a referent and thereby facilitate pronoun interpretation.